NUMERICAL AND EXPERIMENTAL MODELING OF INTERACTION BETWEEN A TURBULENT JET FLOW AND AN INLET - Lien, H. D.; Antonov, I. S. (Vietnam Journal of Mechanics, 2000)
In ventilation devices to get rid of harmful substances out of workingplaces, we use sucking devices. The local sources of pollution are evacuated by them. Abasic element when creating the model of sucking device is: the source of harmful substancesis discussed as a rising convective flow, which is ejected out of sucking spectrum,created by a sucking apparatus. In the present work, the flow is a whole one with variablequantity of motion and kinetic energy along it's length. The change in those twoparameters is caused by and is in dependent function of the inlet spectrum. There hasbeen discussed a two-component flow of air and gas in ventilation devices. A two-velocityscheme of flow is used to realise the numerical method. An integral method of investigationis used, based on the conditions of conservation of mass contents, quantity of motion andkinetic energy. It's been accepted that quantity of motion and energy change in functionof inlet action. A comparison of numerical results and natural experiment are made fortwo conditions: full suck and not full suck. Conclusion is that the present model is preciseand can be unset for engineering calculations.